Distribution of amoebal endosymbiotic environmental chlamydia Neochlamydia S13 via amoebal cytokinesis. (16th February 2021) - Okude, Miho; Matsuo, Junji; Yamazaki, Tomohiro; Saito, Kentaro; Furuta, Yoshikazu; Nakamura, Shinji; Thapa, Jeewan; Okubo, Torahiko; Higashi, Hideaki; Yamaguchi, Hiroyuki
Abstract: We previously isolated a symbiotic environmental amoeba, harboring an environmental chlamydia, Neochlamydia S13. Interestingly, this bacterium failed to survive outside of host cells and was immediately digested inside other amoebae, indicating bacterial distribution via cytokinesis. This may provide a model for understanding organelle development and chlamydial pathogenesis and evolution; therefore, we assessed our hypothesis of Neochlamydia S13 distribution via cytokinesis by comparative analysis with other environmental Chlamydiae ( Protochlamydia R18 and Parachlamydia Bn9 ). Dual staining with 4′, 6‐diamidino‐2‐phenylindole and phalloidin revealed that the progeny of Neochlamydia S13 and Protochlamydia R18 existed in both daughter cells with a contractile ring on the verge of separation. However, in contrast to other environmental Chlamydiae, little Neochlamydia S13 16S ribosomal DNA was amplified from the culture supernatant. Interestingly, Neochlamydia S13 failed to infect aposymbiotic amoebae, indicating an intimate interaction with the host cells. Furthermore, its infectious rates in cultures expanded from a single amoeba were always maintained at 100%, indicating distribution via cytokinesis. We concluded that unlike other environmental Chlamydiae, Neochlamydia S13 has a unique ability to divide its progeny only via host amoebal cytokinesis. This may be a suitable model to elucidate the mechanism of cell organelle distribution and of chlamydial pathogenesis and evolution.